The correlation between peltier module, solution volume and temperature in iot-controlled hydroponic nutrient solution management - Sulaiman, Hamdan; Yusof, Ahmad Anas; Mohamed Nor, Mohd Khairi (2023)
This paper presents the study to determine the correlation of factors considered in developing a temperature control system that remotely controls the heating and cooling process of a hydroponic nutrient solution (HNS). The system incorporates the use of the Internet of Things (IoT), to remotely monitor, control, and acquire data. The ESP32 is used to provide IoT connectivity through the Blynk application. The temperature measurements were collected using the DS18B20 temperature sensor. The number of Peltier modules utilized for both heating and cooling cores varies from 1 to 4 units, as well as the volume of solution employed, varies between 1000 ml, 1500 ml, and 2000 ml, respectively. The heating and cooling performances were evaluated by determining the thermal equilibrium temperature meanwhile the correlation was analyzed using a fit regression model. The highest and lowest temperature recorded are 67.36 °C and 11.88 °C, respectively, with the uses of 4 Peltier modules as the temperature regulation core. Furthermore, the result reveals that the number of Peltier modules factor has significant affect (P < 0.05) on both of the heating and cooling capabilities of the system meanwhile the volume of the HNS factor is only significant for cooling performance (P = 0.023) compared to heating performance (P = 0.205). The correlation of the factors is represented by the regression model.